Synthesis and Ultraviolet Visible Spectroscopy Studies of Chitosan Capped Gold Nanoparticles and Their Reactions with Analytes - Norfazila Mohd Sultan; Mohd Rafie Johan (The Scientific World Journal)
Gold nanoparticles (AuNPs) had been synthesized with various molarities and weights of reducing agent, monosodium glutamate (MSG), and stabilizer chitosan, respectively. The significance of chitosan as stabilizer was distinguished through transmission electron microscopy (TEM) images and UV-Vis absorption spectra in which the interparticles distance increases whilst retaining the surface plasmon resonance (SPR) characteristics peak. The most stable AuNPs occurred for composition with the lowest (1 g) weight of chitosan. AuNPs capped with chitosan size stayed small after 1 month aging compared to bare AuNPs. The ability of chitosan capped AuNPs to uptake analyte was studied by employing amorphous carbon nanotubes (α-CNT), copper oxide (Cu2O), and zinc sulphate (ZnSO4) as the target material. The absorption spectra showed dramatic intensity increased and red shifted once the analyte was added to the chitosan capped AuNPs.